Kajian Karya Poster ''Comic Frontier 13'' Oleh Faiz Azhar - Arifin, Syifa Aura (Magenta | Official Journal STMK Trisakti, 2024)
This article aims to analyze the "Comic Frontier 13" poster from a design perspective designed by Faiz Azhar, a freelance designer and illustrator. This poster is a work that answers a problem or fulfills a client's wishes, depicts the life of a futuristic modern society and highlights the anime community or Japanese culture in Jakarta and its surroundings. The research uses qualitative methods with design thinking theory which includes the Empathize, Define, Ideate, Prototype and Test stages. The process of making a poster involves discussion with the client, determining a theme, exploring ideas, and implementing it in prototype form. The result is a key visual that is not only visually attractive but also reflects the futuristic city of Jakarta with the style of famous characters from Japanese culture, namely Anime characters. This article provides insight into the creative process in poster design, from understanding the client's needs to visual implementation. The success of this poster can be seen from the positive response from visitors, confirming the importance of design thinking in creating work that fulfills client desires and responds to the needs of the target market. This shows that design thinking can be an effective approach in designing meaningful work. Abstrak Artikel ini bertujuan untuk menganalisis poster "Comic Frontier 13" dari perspektif desain yang dirancang oleh Faiz Azhar, seorang desainer dan illustrator freelance. Poster ini menjadi karya yang menjawab permasalahan atau memenuhi keinginan klien, menggambarkan kehidupan masyarakat modern futuristik dan menghighlight komunitas Anime atau budaya Jepang di Jakarta dan sekitarnya. Penelitian menggunakan metode kualitatif dengan teori desain thinking yang mencakup tahap Empathize, Define, Ideate, Prototype dan Test. Proses pembuatan poster melibatkan pembahasan dengan klien, penentuan tema, eksplorasi ide, dan implementasi dalam bentuk prototype. Hasilnya adalah key visual yang tidak hanya visual menarik tetapi juga merefleksikan kota Jakarta yang futuristik dengan style karakter terkenal dari budaya jepang yaitu karakter Anime. Artikel ini memberikan wawasan tentang proses kreatif dalam desain poster, dari pemahaman kebutuhan klien hingga implementasi visual. Keberhasilan poster ini dapat dilihat dari respon positif pengunjung, menegaskan pentingnya desain thinking dalam menciptakan karya yang memenuhi keinginan klien dan merespon kebutuhan target pasar, hal ini memperlihatkan bahwa desain thinking dapat menjadi pendekatan yang efektif dalam merancang karya yang berarti.